2014
DOI: 10.1063/1.4896330
|View full text |Cite
|
Sign up to set email alerts
|

Measuring thermal conductivity of polystyrene nanowires using the dual-cantilever technique

Abstract: Thermal conductance measurements are performed on individual polystyrene nanowires using a novel measurement technique in which the wires are suspended between two bi-material microcantilever sensors. The nanowires are fabricated via electrospinning process. Thermal conductivity of the nanowire samples is found to be between 6.6 and 14.4 W m(-1) K(-1) depending on sample, a significant increase above typical bulk conductivity values for polystyrene. The high strain rates characteristic of electrospinning are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…It is reported that strengthening the electric field is beneficial to enhance the chain alignment, and thus the thermal conductivity of the electrospun PE nanofibers 10 [26,27]. According to the degree of polymer chain alignment in an electrospun fiber, Canetta et al [28] summarized the possible orientations of the chains in a polymer as shown in Fig. 6.…”
Section: Electrospinningmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that strengthening the electric field is beneficial to enhance the chain alignment, and thus the thermal conductivity of the electrospun PE nanofibers 10 [26,27]. According to the degree of polymer chain alignment in an electrospun fiber, Canetta et al [28] summarized the possible orientations of the chains in a polymer as shown in Fig. 6.…”
Section: Electrospinningmentioning
confidence: 99%
“…(b) a core-shell morphology with the shell formed by aligned chains and core comprised of randomly oriented chains; (c) a super-molecular morphology with aligned-chain grains filled in a randomly oriented chain matrix. [28] Copyright 2014 American Institute of Physics. Figure 7 shows the enhanced thermal conductivity of polymers with chain alignment through different processing techniques.…”
Section: Fig 6 Orientations Of Polymer Chains: (A) a Nanofiber With mentioning
confidence: 99%
“…A variety of methods, such as 3ω method 23 24 , Raman spectroscopy 25 26 27 , and cantilever techniques 13 28 , can be used to characterize the thermal properties of materials in micro/nano scale. In our experiment, because PSQ crystals are in regular beam shapes, a suspended micro thermal device is implemented to characterize the thermal properties 29 30 31 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the alignment of polymer chains by electrospinning can achieve a 20-fold enhancement of the thermal conductivity. 116 Recently, electrospun CdSe/ZnS QDs-PS hybrid nanofibers have been prepared and packaged on chip on board (CoB) LEDs. 113 In comparison to the traditional QDs-PS membrane, the CdSe/ZnS QDs-PS hybrid nanofibers membrane shows an enhancement of around 55.4% and 481.3% for the through-panel and in-panel thermal diffusivities, respectively.…”
Section: Diodesmentioning
confidence: 99%